Flexural performance of reinforced carbon nanofibers enhanced lightweight cementitious composite (CNF-LCC) beams - Wang, Su (2022)
As a type of lightweight concrete, foam concrete is traditionally used for non-structural applications due to its poor mechanical properties. However, in recent years, there is a surge in interest in potential applications of foam concrete as structural components due to its low self-weight, homogenous foam bubble distribution, self-compacting, saving in raw materials, good thermal and acoustic insulation. The main challenge for foam concrete is to have high-performance pore walls to provide required mechanical properties, shrinkage resistance, and durability under reduced density. A new type of foam concrete termed as carbon nanofibers enhanced lightweight cementitious composite (CNF-LCC) was developed and reported to have excellent mechanical properties, bond strength with steel reinforcement, durability and shrinkage resistance compared with traditional foam concrete. In this paper, the flexural performance of 8 reinforced CNF-LCC beams was investigated. Test parameters included the amount of carbon nanofibers (CNFs), tension and compression reinforcement ratios, and steel link ratio. The flexural performance of reinforced CNF-LCC beams was comparable with that of normal weight concrete (NWC) and lightweight aggregate concrete (LWAC) and even exceeded traditional foam concrete. The usual reinforcement detailing for NWC beams can be equally employed on CNF-LCC beams. Incorporation of CNFs produced varying degrees of improvement on flexural response especially ductility of beams. Finally, predictions from standard codes and the proposed model agreed well with the test results.